Forecasting Kebutuhan Rak Peyimpanan Rekam Medis Tahun 2025 Di Rumah Sakit Angkatan Udara Dr M. Salamun - Siti Sarah Rohimah; Leni Herfiyanti (Jurnal Delima Harapan, 2022)
One of the medical record service tools is a medical record storage rack. This is used to store medical recprd in a safe and confidential place, considering that the medical record them selves are original and protected by law. With a shelf that fits the storage capacity, this will not occur in the accumulation of medical record documents. Therefore, the research aims to determine the need for medical record storage racks for the next five years at the dr. M Salamun hospital. The type of research carried out using descriptive methods, and data collection methods with observation and documentation, the subjects used in this study were medical record files and the number of patient in a year. From the results obtained by researchers, new patients one day reaced 43 patients. As for the storage area of 102m2 and has 14 available shelves. With a distance between shelves of 80cm, with this, this researcher forecasts the need for shelves for the next years so that documents do not accumulate or scatter. And produced for 2025 forecasting as many as 5 shelves and an additional 62m2 square of the area.